Advances in ecopolitics. Vol. 1 - Leonard, Liam. (Bingley, U.K. : Emerald, 2007)
Since the 17th century people have sought out utopias, establishing communities towards this aim. In the UK and US, educational institutions and planned communes were developed. Many were seeking to establish green alternative lifestyles or agrarian co operatives. Others reclaimed land or settled in areas once populated and then abandoned, providing a new lease of life for rural areas. Ireland has witnessed these patterns of utopian resettlement from the establishment of gaeltachts in the 1920s through to the influx of environmentally minded idealists from the UK or Germany to the west during the 1970s and 1980s. More recently, communities have emerged around protest sites in Rossport, the Glen of the Downs, Carrickmines and Tara and an Ecovillage in Tipperary has been established.
Introduction / Liam Leonard -- Imperfect utopias : green intentional communities / Lucy Sargisson -- Towards an ecological art of living : on the value of ecological utopianism for our future / Marius DeGeus -- Alternative currencies as localised utopian practice / Peter North -- Elusive escapes? : everyday life and ecotopia / Jon Anderson -- Towards a concrete utopian model of green political economy : from economic growth and ecological modernisation to economic security / John Barry -- Sustaining ecotopias : identity, activism and place / Liam Leonard -- Building utopia here and now? : left and working-class utopias in Ireland / Laurence Cox -- Trying to make sense : campaigns and the structure of discursive opportunities / Mark Garavan -- Power to the people? : assessing democracy in Ireland / Michael Ewing -- Assessing democracy in Ireland / Liam Leonard.
Keywords: Environmental policy; Political ecology